Assessment of a pond for oyster hatchery development in South Africa - Simmons, Aron (Marine Research (MA-RE) Institute, 2015)
This study assessed a man-made salt-water pond (saltwater pond 1 SP1) as a potential site for the development of an oyster hatchery in Velddrif, South Africa. Over the study period it was observed that the site was not suitable for oyster larvae culture due to the following factors: temperature spikes during the summer months, low dissolved oxygen levels, high salinity levels, and the proliferation of the filamentous green algae (FGA), mainly the sp. Rhizoclonium implexum. Widespread patches of R. implexum were observed within SP1 and increased in biomass over the study period. Biomass patterns were not measured within this study, however microcosm experiments directed at nutrient depletion rates caused by FGA proliferation assessed the effect of the FGA on the system. Within microcosm experiments with and without FGA, nitrite within the system was significantly lower in the FGA inclusion treatment. Pond nutrient dynamics within the system indicated that widespread nutrient depletion occurred between the incoming water and the rest of the pond, and it was clear that the inflow station had significantly higher nutrient concentrations than all the other stations within SP1. Phytoplankton concentrations were extremely low and could be attributed to the FGA dominated state within SP1. Taken together with the fact the water levels within SP1 were not stable, the data suggested that SP1 was not an optimal source of seawater for either algal or larval oyster culture, and an alternative oyster hatchery site should be assessed.